2013
DOI: 10.1016/j.colsurfb.2013.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Formulation optimization of palm kernel oil esters nanoemulsion-loaded with chloramphenicol suitable for meningitis treatment

Abstract: Palm kernel oil esters nanoemulsion-loaded with chloramphenicol was optimized using response surface methodology (RSM), a multivariate statistical technique. Effect of independent variables (oil amount, lecithin amount and glycerol amount) toward response variables (particle size, polydispersity index, zeta potential and osmolality) were studied using central composite design (CCD). RSM analysis showed that the experimental data could be fitted into a second-order polynomial model. Chloramphenicol-loaded nanoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 36 publications
2
47
0
2
Order By: Relevance
“…The chloramphenicol-loaded NE palm kernel oil esters were developed by evaluation of different levels of oil, lecithin and glycerin. It was observed that the droplets sizes were most affected by the amount of oil, while the proportions of lecithin and glycerin modified ZP and osmolarity (Musa et al, 2013).…”
Section: Ne Containing Eucalyptus Oil (Eucalyptus Globulus)mentioning
confidence: 95%
See 1 more Smart Citation
“…The chloramphenicol-loaded NE palm kernel oil esters were developed by evaluation of different levels of oil, lecithin and glycerin. It was observed that the droplets sizes were most affected by the amount of oil, while the proportions of lecithin and glycerin modified ZP and osmolarity (Musa et al, 2013).…”
Section: Ne Containing Eucalyptus Oil (Eucalyptus Globulus)mentioning
confidence: 95%
“…The chloramphenicol-loaded NE palm kernel oil esters were developed by evaluation of different levels of oil, lecithin and glycerin. It was observed that the droplets sizes were most affected by the amount of oil, while the proportions of lecithin and glycerin modified ZP and osmolarity (Musa et al, 2013).Studies on NE prepared with VO of babassu, rapeseed, rapeseed/salmon, orange/terpene orange, tea tree, grape seed/almond kernel and pomegranate were also developed for their use as potential matrices for incorporation of cosmetic and/or pharmaceutical active elements.Babassu oil NE (Orbignya oleifera) were prepared employing the PIT method. During the process of preparation different temperatures were tested, but only 75 ± 5 ºC provided stable formulations, with transparent bluish luster.…”
mentioning
confidence: 99%
“…This results in larger particle formation. 38 Xanthan gum, which acted as the thickening agent, was able to reduce homogenization efficacy, due to difficulty during the emulsification process.…”
mentioning
confidence: 99%
“…This could be due to the incomplete coverage of the fixed amount of emulsifier molecules on the newly formed droplets, leading to an increase in the particle size of an emulsion. 21,66,67 Moreover, an increase in mixing rate (P,0.05) slightly decreased droplet size ( Figure 9B). These results were in good agreement with reports that the influence of mixing rate is more pronounced at high addition rates and that low addition rates and high mixing rates favor the formation of emulsions with small droplet size.…”
mentioning
confidence: 99%
“…Response surfaces and 3D contour plots of the fitted polynomial-regression equations were generated to visualize the interaction effect of the independent variables on responses better. 21 …”
mentioning
confidence: 99%